A Peran Pusat dalam Interaksi Sosial dan Pemeliharaan Budaya Lokal dalam Warisan Bahasa Widal Kota Sukabumi: Peran Pusat dalam Interaksi Sosial dan Pemeliharaan Budaya Lokal dalam Warisan Bahasa Widal Kota Sukabumi - Chisa Belinda Harahap; Muhammad Guntur Muntaha; Moh. Dulkiah (UNIB Press, 2024)
This research reveals the phenomenon of Indonesian culture through the Widal Sukabumi language in Tipar, Sukabumi City, West Java, by highlighting the role of this language in social interaction and local culture. This research aims to reveal the role of the Widal language in maintaining local culture, trace patterns of social interaction in the Tipar Sukabumi community, and identify traces of Indonesian culture that are reflected in the linguistic structure of Widal Sukabumi. Qualitative methods were used by interviewing native speakers of the Widal language, literature studies, and videos documentary as a data source. The research results show that the Widal language was formed as a code language in the Dutch East Indies era. This language structure reflects traces of Indonesian culture with local vocabulary and traditional expressions. The Widal language is not only a means of communication, but also a linguistic cultural heritage that strengthens community solidarity. The unique interaction patterns in Tipar create a social structure because of the Widal language. The implications of this research increase understanding of the role of the Widal language as a linguistic heritage and a tool for maintaining social interaction.